(3QSGdI aj Yde GdMSGHs
(3ChdgG (B:s
(3hGdKdK hGMO ef KdGKI hGdQHY hGMO ef CQHYI s
(3BNQgG (B:s
(3aEPG aQZ GdJVdjY hGdcShQ aQLJ GdUMGM hbO JeJ hUMMJ s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdSGOSIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3eOQSI GdMLjGJ (B_ (3GdehUd (B(18/265) s
Keywords: (3GdadSaI hGdefWbs